Prepare for anything survival manual - MacWelch, Tim (Weldon Owen, Incorporated, 2014)
"Are you preparing for the collapse of society? If so, you are definitely not alone. In this timely follow-up to The Ultimate Survival Manual, Prepare for Anything is packed with hundreds of gear, skills, and survival tips and strategies to help you be ready for anything, from economic collapse and terrorism to natural disasters and government surveillance."--